PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUALTERHADAP KINERJA KARYAWAN - Riani, Winda Desta; Suryani, Ni Nyoman; Parwita, Gde Bayu Surya (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Organizational objectives can be achieved maximally if supported by good performance from employees within the organization. To get good performance from employees, a structured and effective direction must be sought to move its employees to want to work more productively in accordance with the organization's stated goals, many factors that influence the performance of employees including intellectual intelligence, emotional intelligence, and spiritual intelligence. This research was conducted with the aim of